Immunogenicity and structural efficacy of P41 of Plasmodium sp. as potential cross-species blood-stage malaria vaccine. (June 2021) - Ramanto, Kevin Nathanael; Nurdiansyah, Rizky
Abstract: Vaccine based strategies offer a promising future in malaria control by generating protective immunity against natural infection. However, vaccine development is hindered by the Plasmodium sp. genetic diversity. Previously, we have shown P41 protein from 6-Cysteine shared by Plasmodium sp. and could be used for cross-species anti-malaria vaccines. Two different approaches, ancestral, and consensus sequence, could produce a single target for all human-infecting Plasmodium . In this study, we investigated the efficacy of ancestral and consensus of P41 protein. Phylogenetic and time tree reconstruction was conducted by RAXML and BEAST2 package to determine the relationship of known P41 sequences. Ancestral and consensus sequences were reconstructed by the GRASP server and Unipro Ugene software, respectively. The structural prediction was made using the Psipred and Rosetta program. The protein characteristic was analyzed by assessing hydrophobicity and Post-Translational Modification sites. Meanwhile, the immunogenicity score for B-cell, T-cell, and MHC was determined using an immunoinformatic approach. The result suggests that ancestral and consensus have a distinct protein characteristic with high immunogenicity scores for all immune cells. We found one shared conserved epitope with phosphorylation modification from the ancestral sequence to target the cross-species vaccine. Thus, this study provides detailed insight into P41 efficacy for the cross-species anti-malaria blood-stage vaccine.